Pengaruh Motivasi, Disiplin dan Lingkungan Kerja terhadap Kinerja Karyawan CV Nusantara Garment Surabaya - Santoso, Bowo; Anggraini, Tania Bella (Universitas Batanghari Jambi, 2025)
This research was conducted to examine the correlation between motivation, work discipline, and work environment and their impact on employee performance in the sewing division of CV Nusantara Garment Surabaya. Data collection methodology employed in-depth interview techniques and distribution of research instruments via Likert-scale ordinal questionnaires, engaging 40 respondents within the specified work unit. This study employs saturated sampling technique as a sample selection procedure, with data processing utilizing Partial Least Square (PLS) and Structural Equation Modeling (SEM) methodologies. Research findings reveal a significant and positively correlated relationship between motivation, work discipline, and workplace environmental characteristics impacting employee performance at the stitching division of CV Nusantara Garment Surabaya.